Fagradalsfjall (Iceland) 2021 Eruption Ground Control Points (GCPs) - Christopher W. Hamilton; Birgir Óskarsson; Guðmundur Valsson; Michael Steven Christoffersen; Joana Ruth Charlotte Voigt; William Moreland; Nathan Hadland; Alexia Kubas; Brett Carr (2022)
This item contains the names and location of Ground Control Points (GCPs) used to georeference UAS surveys conducted during the 2021‒2022 eruption Fagradalsfjall eruption in Iceland. The GCPs were placed and their locations measured by University of Arizona’s Lunar and Planetary Laboratory scientists and colleagues at the University of Iceland (Háskóli Íslands), Icelandic Institute of Natural History (Náttúrufræðistofnun Íslands), and National Land Survey of Iceland (Landmælingar Íslands). Additional Acknowledgments: For their assistance in the field we thank Dr. Þorvaldur Þórðarson, Dr. Ármann Höskuldsson, Dr. Ingibjörg Jónsdóttir, Dr. Magnús Tumi Guðmundsson, Dr. Gro B. M. Pedersen, and Nils Gies. For inquiries regarding the contents of this dataset, please contact the Corresponding Author listed in the README.txt file. Administrative inquiries (e.g., removal requests, trouble downloading, etc.) can be directed to data-management@arizona.edu This item is part of the Fagradalsfjall (Iceland) Eruption collection